Β-Catenin mediates tumor-induced immunosuppression by inhibiting cross-priming of CD8+ T cells. Issue 1 (10th September 2013) - Liang, Xinjun; Fu, Chunmei; Cui, Weiguo; Ober-Blöbaum, Julia L; Zahner, Sonja P; Shrikant, Protul A; Clausen, Björn E; Flavell, Richard A; Mellman, Ira; Jiang, Aimin
Abstract : Tumors activate β-catenin in DCs to suppress CD8 immunity by inhibiting cross-priming; β-catenin-suppressed CD8 immunity could be rescued by enhancing cross-priming. ABSTRACT: Whereas CD8 + T cells are essential for anti-tumor immunity, tumors often evade CD8 + T cell surveillance by immunosuppression. As the initiators of antigen-specific immune responses, DCs are likely to play a central role in regulating the balance between immunity and tolerance to tumor antigens and are specialized in their ability to cross-present exogenous tumor antigens on MHC class I molecules to initiate CD8 + T cell immunity. However, it remains unclear whether and how tumors modulate DC functions to suppress CD8 + T cell responses. We have shown previously that β-catenin signaling in DCs promotes DC-mediated CD4 + T cell tolerance. Here, we tested the hypothesis that β-catenin in DCs mediates tumor-induced suppression of CD8 + T cell immunity by inhibiting the ability of DCs in cross-priming. β-Catenin was activated in DCs by multiple tumors in vivo and in vitro. B16 melanoma-bearing mice, when vaccinated with DC-targeting anti-DEC-205 mAb fused with tumor antigens, exhibited dampened CD8 + immunity, similar to DC-β-catenin active mice. DCs from DC-β-catenin active and tumor-bearing mice were deficient in cross-priming, and antigen-specific CD8 + T cells primed in these mice resulted in dampened CD8 + memory responses. Importantly, DC-β-catenin −/− mice completely abrogate tumor-mediated inhibition of cross-priming, suggesting that tumor-induced inhibition of cross-priming is dependent on β-catenin. Finally, enhancing cross-priming at the priming or recall phase rescued β-catenin-suppressed CD8 + immunity in DC-β-catenin active and tumor-bearing mice. Thus, β-catenin-mediated inhibition of cross-priming represents a new and potentially general mechanism that tumors employ to achieve immunosuppression.